2009
DOI: 10.1007/s00586-009-1168-5
|View full text |Cite
|
Sign up to set email alerts
|

The association between isoinertial trunk muscle performance and low back pain in male adolescents

Abstract: The literature reports inconsistent findings regarding the association between low back pain (LBP) and trunk muscle function, in both adults and children. The strength of the relationship appears to be influenced by how LBP is qualified and the means by which muscle function is measured. The aim of this study was to examine the association between isoinertial trunk muscle performance and consequential (non-trivial) low back pain (LBP) in male adolescents. Healthy male adolescents underwent anthropometric measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 55 publications
1
36
1
1
Order By: Relevance
“…Because most of the studies20 , 32 , 33 are generally focused on excess body weight, it is necessary to evaluate the influence of the non-respondents, but it was not possible to carry out this procedure, in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Because most of the studies20 , 32 , 33 are generally focused on excess body weight, it is necessary to evaluate the influence of the non-respondents, but it was not possible to carry out this procedure, in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors did not stratify the sample into active and inactive individuals, noting that the practice of sports activities outside the school environment was not associated with the occurrence of low back pain. Nonetheless, Balagué et al [24] reported that adolescents, who were involved in sports programs, had higher chances of the occurrence of low back pain. Sitthipornvorakul et al [25] in a systematic review found no association between physical activity and neck pain, and there is still conflict in the literature when associating physical activity and low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…Diepenmaat et al 33 identificaram que sintomas depressivos e estresse estavam associados à dor no pescoço e nos braços e à dor lombar em adolescentes de 12 a 16 anos. Investigações que utilizaram o mesmo questionário aplicado no presente estudo, também encontraram os fatores psicossociais como associados à dor lombar: maior pontuação total no questionário associou--se à dor nas costas e no pescoço 39 ; a categoria anormal dos sintomas emocionais, em relação à normal, apresentou razão de chance de 1,65 40 ; problemas de conduta e sintomas emocionais se associaram à dor lombar em escolares de 11 a 14 anos 20 ; a variável "problemas de relacionamento com colegas" foi uma das preditoras de dor lombar persistente em estudo de acompanhamento de quatro anos 9 e, também em estudo longitudinal, jovens com problemas de conduta e hiperatividade apresentaram risco aumentado para dor lombar um ano após a avaliação inicial 41 . A prática de exercício para além das aulas de Educação Física não se associou à ocorrência de dor lombar.…”
Section: Introductionunclassified